Моделювання варіантів проектів інвестиційного забезпечення технологічного оновлення підприємств - Добрянська, М. В. (Видавництво Львівської політехніки, 2015)
Удосконалено метод формування рішення щодо інвестиційного забезпечення технологічного оновлення підприємств. На основі вищенаведеного методу сформовано етапи аналізування і вибору найкращого проекту інвестиційного забезпечення технологічного оновлення серед альтернативних. Запропонований методичний підхід дав змогу вирішити проблему незбалансованості параметрів оптимізації інвестиційних проектів на їх вході та виході поглибленням формалізації інвестиційного забезпечення технологічного оновлення машинобудівних підприємств. For companies, technological updates are accompanied by complex engineering and organizational changes, the implementation of which is inevitably linked to certain capital and operating costs. Because of this, the technological innovation is an investment decision for a company. Meaning that its rationality is measured by the level of an investment efficiency and expected gains from the invested products. Often company’s management decisions are made without sufficient scientific justification. This results in a set of negative effects which can cause an inability to compete or even lead to company’s bankruptcy. Therefore, solving the problem of technological innovation requires managers to apply scientific justification methodology to make these investment decisions. Studies have shown that the existing methods are not sufficiently substantiated. They do not have a well formed logical transition among various forms of the tasks of the alternative technological updates investment projects. They are not capable of choosing the best of them and providing an organizational support for the implementation of the project which is optimal according to various criteria. Also, critical analysis of the existing methodological approaches of the enterprise technological renovation investment support modeling choices showed that their disadvantage is an unbalanced investment projects input and output parameter optimization. This article proposes a methodical approach that allow to solve this problem by deepening the formalization of the investment input into the technological replenishment of the machine building enterprises. It is prove that the execution of this task based on the multi-vector analysis of the suitability of the alternative investment options enables enterprise managers, guided by the criteria of money expenditure and time not only to choose the best option of the technological enterprise renovation investment from a number of existing options, but also to build an optimal sequence of the project work implementation events, which contributes to rationalizing investment decisions.
Modeling options of investment support projects of technological renovation of enterprises
Keywords: інвестиційне забезпечення; технологічне оновлення; інвестиційний проект; інвестиційні рішення; investment support; technological innovation; investment projects; investment decision